Patent Urachus and Associated Comorbidities in 101 Newborn Foals: A Retrospective Study - André Bernick; Judith Krohn; Axel Wehrend (Veterinary Medicine and Science)
ABSTRACT Background Patent urachus is a common disease in newborn foals. However, despite its frequency, studies investigating symptoms, comorbidities, treatment and prognosis in a large number of affected foals have rarely been conducted. Objective This study aimed to describe the clinical symptoms, laboratory diagnostic findings and prognosis of foals with patent urachus. Method Data from 101 foals with a patent urachus from 2006 to 2017 were analysed. Results Patent urachus occurred at a frequency of 7.8% of all foals up to the 14th day of life during the study period. More colts (74.3%) than fillies (25.7%) were affected. In those with secondary urachal fistulae, patent urachus (91.1%) was significantly more diagnosed than persistent urachus (8.9%). Typical symptoms were a moist external umbilical environment (100%) and urine dripping from the external umbilical cord remnant during urination (75%). The average age at the time of diagnosis was 5.5 ± 3.2 days (median: 5 days, range: <1–13 days). Umbilical resection was performed in 29.7% of foals, whereas 70.3% were treated conservatively. In total, 67.3% of affected foals were discharged from the clinic. Foals that underwent umbilical resection were discharged in 76.7%, and those that underwent conservative treatment in 63.4% of cases. No typical laboratory diagnostic findings related to patent urachus could be determined. However, an elevated lactate concentration on the day of admission was linked to significantly worsened prognosis (p = 0.021). In 18.5% of the foals, which received surgery, a wound‐healing complication occurred at the abdominal suture. Further, 67% of the foals had one or more comorbidities. The presence of musculoskeletal disorders significantly worsened the survival prognosis (p = 0.037). In total, 46 foals were monitored for at least 6 months (6 months to 10 years) after discharge from the clinic. At this point, 93.9% of the foals were alive, and none developed any further health complications with the umbilicus or abdominal sutures. Conclusion The primary result of this article is that patent urachus has a limited statistical influence on clinical parameters, laboratory values and prognosis. Comorbidities and/or sequelae worsen survival prognosis. The prognosis in the first 6 months after discharge was very good.